Introduction to Standard-Driven Co-Simulation Architectures - Krammer, Martin; Schiffer, Clemens; Benedikt, Martin (Center for Model-Based Cyber-Physical Product Development, 2021)
The Functional Mock-Up Interface (FMI) and the Distributed Co-Simulation Protocol (DCP) are two important Modelica Association standards. Both address the topic of system simulation. On one hand, FMI is used to encapsulate local software components representing simulation models. On the other hand, DCP is a platform and communication system independent application level communication protocol. It is intended for encapsulation of models or real-time systems. Both FMI and DCP are compatible to each other by design. In this talk, we address the problem of defining co-simulation architectures. We will show how both standards can be combined in a reasonable way to generate effective architectures for co-simulation. We introduce the most important architectural patterns for co-simulation and discuss their advantages and disadvantages. Goal is to reduce the overall system development effort. Re-use of existing development artefacts, like high-quality FMUs, is of high priority. Furthermore, architectural patterns foster modular development. The introduced architectural patterns can be deployed to numerous applications. Examples include distributed numeric calculation, hardware-in-the-loop testing, or mixed real-virtual development approaches. FMI is developed by a large community of simulation experts and is supported by more than 100 commercial and non-commercial software tools. Tool support for DCP is emerging, first software tool providers are listing their tools as DCP-supporting tools. In this context, appropriate architectures for co-simulation will become more significant in the future.